A Study of Feminine Identity Crisis in Anita Desai’s Fictional Work - Akter, Ferdousi (International Journal of Applied and Scientific Research, 2024)
This research delves into Anita Desai's literary exploration of the feminine identity crisis, examining how her novels depict women's battles against societal and familial restrictions. Through an intersectional feminist perspective, Desai's works, including Fire on the Mountain, Cry the Peacock, and Voices in the City, are analyzed to reveal the enduring perception of women's inferiority and their roles as sacrificial figures within the family structure. Employing a descriptive methodology and drawing from primary sources and socio-psychological frameworks, this study interprets Desai's portrayal of women's struggles for autonomy amidst societal pressures. Through thematic exploration and character analysis, it uncovers the nuances of female experiences, their quest for identity, and the entrenched influence of patriarchal norms. Ultimately, the research illuminates Desai's depiction of women's resilience and their journey toward emancipation in the face of systemic oppression.